Autoimmune glial fibrillary acidic protein astrocytopathy misdiagnosed as intracranial infectious diseases: case reports and literature review - Bai, Runhua; An, Li; Du, Wei; Wang, Zhiwei; Qi, Xiaokun; Liu, Jianguo; Ren, Ming; Yu, Yingxin (Frontiers in Immunology, 2025)
BackgroundAutoimmune glial fibrillary acidic protein astrocytopathy (A-GFAP-A) is an autoimmune central nervous system(CNS) disease characterized by GFAP IgG as a biomarker. Several cases of individuals with A-GFAP-A initially misdiagnosed as infectious diseases of the central nervous system have been reported in research. We report three cases of A-GFAP-A misdiagnosed as viral meningitis or tuberculous meningitis (TBM). We summarize recent cases of A-GFAP-A misdiagnosed as central nervous system infections through a literature review.Materials and methodsThree cases of A-GFAP-A were initially misdiagnosed as tuberculous or viral meningitis. Their diagnoses of A-GFAP-A were confirmed with positive GFAP-IgG in cerebrospinal fluid (CSF). We searched the PubMed database with the key words of “GFAP astrocytopathy”, “GFAP autoimmunity”, “GFAP autoantibody”, “intracranial infection”, “meningitis”, “misdiagnose”, and within the literature from Jan 1, 2015 to Mar 15, 2024, 40 cases with A-GFAP-A with positive GFAP-IgG in CSF who were previously misdiagnosed with intracranial infection were reported. The causes of misdiagnoses were summarized and analyzed.ResultsCase 1 was a 41-year-old female, presenting with headache, fever, diplopia, and altered consciousness level. Anti-tuberculosis treatment was ineffective. Finally, with positive GFAP IgG in CSF, she was diagnosed with A-GFAP-A. Case 2 was a 74-year-old male, presenting with fever, excessive sweating, fatigue, and memory loss. Anti-tuberculosis treatment was ineffective. With positive GFAP IgG in CSF, he was diagnosed with A-GFAP-A. Case 3 was a 54-year-old male, presenting with fever, personality changes, and memory decline. Antiviral treatment was ineffective. His diagnosis was revised to A-GFAP-A after testing positive for GFAP IgG in CSF. Our study summarized a total of 40 patients with A-GFAP-A who were initially misdiagnosed as intracranial infections. The most common clinical phenotypes among 40 patients were mimicked meningitis, meningoencephalitis, meningoencephalomyelitis, encephalitis and encephalomyelitis.ConclusionA-GFAP-A is a specific autoimmune meningoencephalomyelitis associated with GFAP-IgG, with lesions involved the brain, meninges, and spinal cord. It commonly presents with symptoms such as fever, headache, altered consciousness, tremor, seizures, and autonomic dysfunction. Brain MRI often shows characteristic linear perivascular radial enhancement perpendicular to the ventricles or nonspecific leptomeningeal enhancement. Early detection of GFAP-IgG in serum and CSF is essential for differential diagnosis.